Exploratory data analysis for almost everyone - Shitan, Mahendran; Vazifedan, Turaj (Universiti Putra Malaysia Press, 2011)
This book is intended to introduce the rudiments of the techniques of Exploratory Data Analysis (EDA) for anyone who is interested in data analysis. The book is simple enough to reach not only undergraduate students but also very wide audience.